How does transit-oriented development affect a neighborhood?: A look into gentrification and displacement - Akowuah, Enoch (Kansas State University, 2021)
The construction of light rail transit lines accompanied by transit-oriented developments improves neighborhoods and makes them attractive and desirable. These developments can also cause property values and rents to go up, making it difficult for low-income residents to stay, which can cause transit-oriented gentrification, as identified by some studies. Historically, low-income households have benefited from living close to station areas since they get cheap and easy accessibility to places. Hence, the vulnerable, including low-income households, adults with lower levels of education, and historically marginalized races, remain at risk of displacement when there is a socio-economic change to a more affluent group around these station areas. Previous studies have always sort to identify gentrification and displacement in low-income and dominated historically marginalized race neighborhoods. However, there have been a lot of challenges for researchers finding the right data and methods to measure gentrification and displacement. This study using simple local percentage share identifies gentrification and displacement in a moderate-to-high income white dominated neighborhood along the Southwest Light Rail Line in the Denver area. The study also tries to identify if the few vulnerable people in the neighborhood are displaced after a new transit development is introduced. The study adopts a pretest-posttest analysis to predict if the corridor undergoes gentrification before the construction of the LRT or after it is built. The study spans from 1990 to 2018 with analysis on changes in 1990-2000, 2000-2010, and 2010-2016. Two methods using simple quantitative analyses like percentage change, local percentage share, absolute figures, and location quotient are employed in this study. The first method uses the conventional method to identify gentrification, which scholars like Freeman (2005) and Chapple et al. (2017) have also used. The conventional method showed that the corridor was susceptible to gentrification through the study period but did not find the area to be gentrifying though there were signs of it. The flaw of the method ignoring the local shift from previous years influenced the adoption of the local share method. The local share method rather showed that the corridor gentrified in the 2010-2016 decennial period. The local share method identified gentrification by showing that the there is a five percentage point changes in the share of low-income households; share of adults with high school certificates or lower; the share of multi-family units; and the percentage increase of rent from the previous period. The study shows the share of adults with high school certificates or lower continuously reduced from 50% to 27% by the end of the study. Also, it was observed that before the construction of the LRT line in 2000, rents reduced to $785 but increased exponentially after the line was built to $1332. The study observed that, the share of new houses and multi-family units begun to increase after the opening of the line. The share of low-income households at the end of the study remained the same as the beginning, whiles the share of high-income households increased by 7 percentage points at the end of the study. No evidence of displacement was observed among non-white race and low-income households along the corridor. However, the reduction in the share of adults with high school certificates or lower and low-income households, whiles those with some college education and middle-income households remained the same, shows that there were some forms of displacement. This study also shows that in unique places like Denver, the conventional method of identifying gentrification and displacement does not show the true characteristics of transit induced gentrification as the local share method does. Also, the study shows that the construction of a new transit infrastructure may not be so hostile to historically marginalized races and sometimes bring about racial diversity as observed along the LRT corridor.
Keywords: Gentrification; Displacement; Transit-Oriented Development; Transit Induced Gentrification; Light rail transit line